Stigmasisasi “Perempuan Alat” di Borong, Manggarai Timur Ditinjau dari Perspektif Filsafat Karol Wojtyla - Suhardi, Akrimianus; Puplius Meinrad, Buru; Widyawati, Fransiska (Unika Santu Paulus Ruteng, 2025)
Women workers in the entertainment sector, such as pubs, are particularly vulnerable to discriminatory treatment and stigmatization from society. This issue is also prevalent among women in Borong. This study explores the community's views in Borong, East Manggarai, regarding their perceptions of women pub workers through the lens of Karol Wojtyla's philosophy. Utilizing a qualitative method, data was collected through in-depth interviews with community members. The community's perspectives from the field research were then analyzed in the context of Wojtyla's philosophical thoughts on persona. The study found that women workers in Borong's pub entertainment sector do experience societal stigmatization. The most common stigma involves labeling them as